RETRACTED: Eruptive lentiginosis in resolving psoriatic plaques - Robert Micieli, BSc; Afsaneh Alavi, MSc, MD, FRCPC (Elsevier, 2018)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy).The above-referenced article has been voluntarily retracted by the authors who subsequent to publication learned that the patient was taking the medication Ustekinumab at the time of the eruption and not Secukinumab. The authors have updated their case report accordingly in a subsequent publication: https://doi.org/10.1016/j.jdcr.2018.07.021.